Effect of ?-irradiation on the growth of ZnO nanorod films for photocatalytic disinfection of contaminated water - Alarcón, Julio (2011)
This work was supported by the Procyt-311-2009 Project and the 321-2009-Concytec-OAJ Project and MINCYT-CONCYTEC PE/ 09/01. We want acknowledge to ‘‘Laboratorio Nacional de Nanotecnologia’’ located at CIMAV and academic technician W. Antunez for help us to acquire SEM images. One of the authors, J. Rodriguez, wishes to thank the ‘‘Convenio de Desempeño, Universidad de Tarapacá-Mineduc’’ for financial support.